Numerical investigation of the performance of a partially wetted geothermal thermosyphon at various power demand schemes. (May 2015) - Hartmann, Frank; Behrend, Ralph; Hantsch, Andreas; Grab, Thomas; Gross, Ulrich
Abstract : Highlights: A transient 2D model for outer region thermal conduction is proposed. Wetting has strong influence on thermosyphon performance. Borehole filling thermal conductivity has strong influence on performance. Extraction/regeneration sequence has strong influence on performance. Abstract: Geothermal thermosyphons utilise the latent heat of a working fluid in order to extract heat from the sub-surface without the requirement of any further mechanical energy. Earlier visual observations showed that the inner pipe area is often not fully wetted by the liquid film. This fact raised the question of the influence on the overall heat transfer of the imperfect wetting in conjunction with the materials of borehole filling (grout) and thermosyphon, and the operational modes. In order to facilitate the discussion, a quasi-three-dimensional model has been developed and solved numerically. The results agree well with experiments and it can be discovered that the choice of the pipe and grout material becomes increasingly important for lower wetting ratios and shorter extraction times. Furthermore, it could be illustrated that a well-wetted polyamide plastic pipe with a thermal conductivity larger than 2 W/(m K) would be a possible alternative to steel pipes.